2021
DOI: 10.3389/fcimb.2021.646467
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiotic Fecal Microbiome in HIV-1 Infected Individuals in Ghana

Abstract: HIV-1 infected individuals under antiretroviral therapy can control viremia but often develop non-AIDS diseases such as cardiovascular and metabolic disorders. Gut microbiome dysbiosis has been indicated to be associated with progression of these diseases. Analyses of gut/fecal microbiome in individual regions are important for our understanding of pathogenesis in HIV-1 infections. However, data on gut/fecal microbiome has not yet been accumulated in West Africa. In the present study, we examined fecal microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 61 publications
5
26
0
Order By: Relevance
“…A few studies also attempted to investigate the exact role played by the gut microbiota in HIV control. Despite gut dysbiosis persistence in HIV-1 infected patients after ART initiation (reduced gut microbial richness and depletion in anti-inflammatory bacteria [ 48 ]), microbial richness may be restored by prolonged ART treatment [ 49 ]. Also, elite controllers, who spontaneously control HIV replication without ART, showed higher gut microbial richness with a metabolic profile resembling that of HIV-uninfected adults [ 50 ] and increased Th17 cells in the gut mucosa compared to ART-treated patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies also attempted to investigate the exact role played by the gut microbiota in HIV control. Despite gut dysbiosis persistence in HIV-1 infected patients after ART initiation (reduced gut microbial richness and depletion in anti-inflammatory bacteria [ 48 ]), microbial richness may be restored by prolonged ART treatment [ 49 ]. Also, elite controllers, who spontaneously control HIV replication without ART, showed higher gut microbial richness with a metabolic profile resembling that of HIV-uninfected adults [ 50 ] and increased Th17 cells in the gut mucosa compared to ART-treated patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased or decreased frequencies of these bacteria were consistent with the findings of many other studies [ 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ]. HIV-associated reduction of the alpha diversity was mainly observed in patients with low CD4 counts [ 143 , 144 , 145 , 146 ]. The restoration of the alpha diversity has been observed in some studies [ 146 , 147 ], while others have found no significant changes after antiretroviral therapy [ 134 , 135 ].…”
Section: Hivmentioning
confidence: 99%
“…There have been several reports showing a relationship between microbial translocation and chronic inflammation using blood markers that support the above observations [ 157 , 158 , 159 ]. Of these, intestinal fatty acid-binding protein, a marker of intestinal disorders, and sCD14, an indirect blood marker of microbial translocation in response to LPS, were associated in a cohort study of HIV-infected individuals [ 144 , 159 ]. These microbial translocation improvements have been shown to potentially affect immune recovery with treatment [ 160 , 161 ].…”
Section: Hivmentioning
confidence: 99%
“…While we failed to detect an effect of a nutritional intervention on the immune parameters, our study was useful to evaluate the associations between longitudinal variations of key microbiota components and inflammatory and immunological parameters. To avoid a large number of comparisons in an unpowered study, we selected bacteria that were differentially abundant in our previous analysis in this cohort of children with HIV (depleted: Faecalibacterium, Lachnospira, Coprococcus, Dorea, Lactococcus, Anaerostipes ; enriched: Coprobacillus ) [ 20 ], along with other key relevant taxa ( Akkermansia, Bacteroides, Bifidobacterium, Butyricicoccus, Eubacterium, Prevotella, Roseburia, and Ruminococcus highlighted as relevant in people living with HIV [ 8 , 10 , 31 , 32 , 33 ]. The findings summarized in Figure 3 , Figure 4 and Figure 5 deserve further comment.…”
Section: Discussionmentioning
confidence: 99%